PERBANDINGAN PERUBAHAN HEMODINAMIK ANTARA INDUKSI PROPOFOL 1 mg/kgBB + KETAMIN 1mg/kgBB DENGAN PROPOFOL 1mg/kgBB +FENTANYL 2Î¼g/kgBB PASCAINTUBASI ENDOTRAKHEA - , ISWORO RINI; , DR. Sudadi, Dr, SpAn, KNA, ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background : Actions of endotrakheal intubation cause hemodynamic changes include increased blood pressure and heart rate. Many attempts medication to stabilize hemodynamic changes, one of which induction with propofol fentanyl. On the use of propofol induction of fentanyl wide hemodynamic changes during induction followed intubation. Propofol-ketamine is a complementary drug combinations based on pharmacodynamic effects are expected to further stabilize the hemodynamic changes in intubasi. The aims of research to known compare the hemodynamic changes induced by the combination of propofol ketamine with intravenous fentanyl and propofol on intubasi. Methode: This study using randomized clinical trials double-blinded, by the number of study subjects as many as 40 patients, ASA physical status I and II effective operation under general anesthesia and endotracheal intubation RS. Dr. Sardjito Yogyakarta, consists of two groups each of 20 patients.Group I received Propofol 1 mg / kg ketamine + 1 mg / kg (PK) and group II, propofol 1 mg / kg + Fentanyl 2 ug / kg intravenously (PF) before laryngoscopy intubation. All patients are given medication midazolam 0.05 mg / kg intravenously, intubation facilities with Rocuronium 0.6 mg / kg intravenously, maintenance with 50% N2O in oxygen and isoflurane 1 vol%. Blood pressure and pulse rate and side effects recorded at minute 1 after induction, and 2 minutes and 5 minutes after intubation. Samples were analyzed with the Student t-test and chisquare with degrees of significance p <0.05. Result : Obtained hemodynamic changes with significant differences in postinduction, decrease in systolic blood pressure (TDS) Group I: II is 10%: 24% with p <0.001, decrease in diastolic blood pressure (TDD) in group I: II = 14%: 20, 8% s with value p = 0.032. Decrease in mean arterial pressure (MAP) in group I: II = 9.8%: 22.35% with a value of p <0.001, decrease in heart rate (HR) group I: II = 6.95%: 12.95% with a value of p = 0029.Significant differences occurred in an increase in the TDD group I: II = 24.95%: 9.65% with a p-value = 0.001. Increase in MAP in group I: II = 21.90%: 30.30% with a value of p = 0.003. Increased HR Group I: II = 23:45%: 14.75% with a value of p = 0.043. Conclusion : Hemodynamic Changes in blood pressure in the PK group is more stable than the PF group, to changes in heart rate (HR) PF group is more stable than the PK group